O romance na educação escolar: reverberações da arte narrativa na concepção de mundo - Costa, Larissa Quachio [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Tanto a vivência estética quanto a atividade educativa não transfiguram a sociedade e a vida do indivíduo de forma direta; mas podem influenciá-las de forma significativa. Diante de tal questão, propusemo-nos a refletir acerca da importância da socialização da literatura realista para o enriquecimento da concepção de mundo do indivíduo. A literatura realista, nesse caso, não diz respeito a um estilo artístico, mas sim à reprodução artística da realidade, à fidelidade ao real, ao esforço apaixonado para reproduzi-lo na sua integridade e em suas relações com a totalidade. Dessa maneira, nossa tese possui como base a hipótese segundo a qual a literatura que contempla os elementos fundamentais da arte realista é aquela que se revela uma “literatura de contestação” e contribui decisivamente para a elevação da concepção de mundo do indivíduo. Ademais, propusemos-nos a analisar não somente a literatura de modo geral, mas um gênero específico: o romance. Importante esclarecermos aqui que nosso objeto de estudo não diz respeito ao romance cujo reflexo da realidade lhe garante a condição de realista. O objetivo deste trabalho é examinar as implicações da referida literatura - no caso, o romance - no desenvolvimento de uma concepção de mundo que possa contribuir para o processo de transformação das relações sociais alienadas e, assim, refletir, à luz da pedagogia histórico-crítica, acerca da urgência da socialização dessa literatura pelas vias da educação escolar, sobretudo pelas vias do Ensino Fundamental II e Médio, para que possa ser devidamente considerada como trabalho educativo que contribui para a formação intelectual e humanística dos indivíduos. Enfim, nossa pesquisa corresponde a um trabalho teórico, fundado no método histórico-dialético, e faz uso da técnica de pesquisa bibliográfica. Nossa discussão sobre a necessidade da arte literária para a formação/transformação da concepção de mundo do indivíduo fundamenta-se no legado de Karl Marx, Friedrich Engels e, principalmente, nas profundas reflexões teóricas de György Lukács. Além disso, nossas reflexões acerca das peculiaridades do grande romance e dos aspectos gerais da literatura apoiam-se nas análises teóricas de estudiosos marxistas como, por exemplo, Adolfo Sánchez Vázquez, Ana Cotrim, Arlenice Alemida da Silva, Carlos Nelson Coutinho, Celso Frederico, José Paulo Netto, Leandro Konder e Ranieri Carli. Além de estudos no campo da estética e da filosofia, apoiamo-nos na seara teórica da pedagogia histórico-crítica, portanto, nas análises teóricas de Dermeval Saviani, Newton Duarte e outros autores cujos estudos sejam pertinentes ao nosso tema.

Both the aesthetic experience and the educational activity do not transform the society and the life of the individual in the direct way; but can influence them significantly. Faced with this question, we proposed to reflect on the importance of the socialization of realistic literature for the enrichment of the world's conception of the individual. Realistic literature, in this case, does not concern an artistic style, but rather the artistic reproduction of reality, fidelity to the real, the passionate effort to reproduce it in its integrity and in its relations with totality. Thus, our thesis is based on the hypothesis that the literature that contemplates the fundamental elements of realistic art is that which reveals itself a “literature of contestation” and contributes decisively to the elevation of the world's conception of the individual. In addition, we proposed to analyze not only literature in general, but a specific genre: the romance. It is important to clarify here that our object of study relates to the romance whose reflection of reality guarantees it the condition of realist. The objective of this work is to examine the implications of the such literature - in this case, the romance - in the development of a conception of the world that can contribute to the process of transformation of alienated social relations and thus reflect, in the light of historical-critical pedagogy , about the urgency of the socialization of this literature through school education, especially through Middle School and High School, so that it can be properly considered as educational work that contributes to the intellectual and humanistic formation of individuals. Finally, our research corresponds to a theoretical work, based on the historical-dialectical method, and makes use of the bibliographic research technique. To support our discussion, the arguments presented in relation to the need of literary art for the formation / transformation of the individual's conception of the world were based the legacy of Karl Marx, Frierdrich Engels, and especially from György Lukacs' profound theoretical reflections. So that we could, in addition to deepening the discussion about the peculiarities of the great novel, also deal with the general aspects of the literature, we resorted to the theoretical analyzes of Marxist scholars such as Adolfo Sánchez Vázquez, Ana Cotrim, Arlenice Alemida da Silva, Carlos Nelson Coutinho, Celso Frederico, José Paulo Netto, Leandro Konder e Ranieri Carli. In addition to studies in the field of aesthetics and philosophy, we rely with the theoretical field of historical-critical pedagogy, therefore, with the theoretical analyzes of Dermeval Saviani, Newton Duarte and other authors whose studies are pertinent to our subject.
The romance in school education: reverberations of narrative art in the worldview
Keywords: Realismo; Literatura; Romance; Pedagogia Histórico-Crítica; Concepção de mundo; Realism; Literature; Romance; Historical-Critical Pedagogy; Worldview